The Restless Whole: on the Polygenesis of the Structural Idea in early twentieth-century Russian Thought (ENTHYMEMA, 2010)
In this essay, I explore the genesis of the concept of literary and artistic work as a whole in early XXth century Russian thought , with special attention to the Formalists and their readings in philosophy. In particular, I emphasize the Russian translation of the German thinker Broder Christiansen’s Philosophie der Kunst, which has become a seminal text of Russian aesthetics, theory of art and theory of literature during the first years of the XX century. In Christiansen’s essay, I focus on the notion of the dominant, that has become widespread thanks to Roman Jakobson. Jakobson's thought reveals its strong teleological matrix, which permeates the Formalists' idea that the work is a whole. I conclude with some brief references to the image of device (“dispositif”), matter of recent discussions within the French cultural context.
Keywords: Russian Formalism; Broder Christiansen; dominant; structure; teleology